Comparação de diferentes critérios para o diagnóstico da periodontite em gestantes - Conceição, Sarah dos Santos (2019)
The pregnant women’s periodontal condition has been the focus of several studies carried in ​​Periodontal Medicine area, consequence of some scientific evidences that points a possible association between periodontitis and gestational dysfunctions. However, there is still no consensus on periodontitis’ diagnosis, making difficult the reliability and comparability of epidemiological studies. Objective: Estimate the diagnostic values ​​of clinical appraisal for the definition of periodontitis in a study database accomplished with pregnant women in the city of Santo Antônio de Jesus, Bahia, Brazil. Taking the following criteria as a gold standard: 1) Page e Eke (2007); Eke et al. (2012), recommended by the Center for Disease Control and Prevention and the American Academy of Periodontology. Method: Validation study, in which the participants were classified according to the presence and severity of periodontitis, according to six proposed criteria, namely: 1) Page e Eke, 2007/2012, 2) Gomes-Filho et al., 2018, 3) Albandar et al., 2007, 4) Bassani et al., 2007, 5) López et al., 2002 and 6) In this et al., 2008. In comparison with the other criteria, the diagnostic values ​​were estimated: sensitivity, specificity, predictive values ​​and likelihood ratio. Results: The findings were presented as articles. In article 01, the frequency of periodontitis ranged from 90.21% to 25.04%, according to the six criteria analyzed. According to the gold standard adopted, the sensitivity of the evaluated criteria ranged from 36% to 98.2%. The specificity ranged from 23.5% to 100%. Conclusion: Based on the used clinical parameters, among the criteria demonstrated for the diagnosis of periodontitis and the evidences on the diagnostic values, the Bassani et al., 2007 one was considered the most sensitive and more suitable for screening the disease. The Gomes-Filho et al., 2018, Albandar et al., 2007, López et al., 2002 and Nesse et al., 2008 criteria were considered more specifics, ideal to confirm this disease.